Dynamic mechanical properties and morphology characteristics of rubber-toughened poly (lactic acid) - Mohd Shaiful Zaidi, Mat Desa; Azman, Hassan; Agus, Arsad; Masleeyati, Yusop (EDP Sciences, 2019)
This study investigates the effect of natural rubber (NR), epoxidised natural rubber (ENR), and core-shell rubber (CSR) as toughening agents for poly(lactic acid) (PLA). PLA/rubber blends were prepared by using melt blending method in a twin-screw extruder, with the content of rubbers was fixed at 5 wt. %. All PLA/rubber blends exhibited lower storage modulus compared to neat PLA. Two-stage storage modulus (E’) was also observed, where the first stage occurred at lower temperature corresponded to the glass transition temperature (Tg) of rubber components, whereas the second E’ corresponded to the Tg of PLA. The impact fracture surface of PLA/rubber blends also exhibited phase-separated morphology where the spherical-shaped rubber particles were clearly present in the PLA matrix.